Strategi Pengembangan Bisnis Makanan Olahan Pada Pesantren Peserta Program OPOP di Kabupaten Bogor - Mohammad Arif Yunus; Sarma, Ma’mun; Baga, Lukman M (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
Islamic boarding school in Indonesia have enormous potentials and roles in terms of numbers, students and resources. This reality is the background for the implementation of the One Islamic Boarding School One Product (OPOP) program for the West Java Provincial Government. This study aims to formulate a strategy for the development of the food industry in Islamic boarding schools participating in the OPOP program in Bogor Regency. The data source for this study comes from primary and secondary data. Primary data were obtained through interviews and filling out questionnaires by Islamic boarding school business managers, similar business actors, OPOP program assistants and expert respondents. Secondary data was obtained from BPS, related agencies and other related literature. The data obtained was then analyzed using SWOT analysis and blue ocean strategy. The results of the research show that the pesantren business has many weaknesses but has various opportunities to be developed. The blue ocean analysis illustrates that the pesantren business is still in tight business competition (red ocean). Therefore, pesantren are recommended to make strategic changes through market penetration and product development strategies. Market penetration strategy through increasing product branding, Islamic boarding school business networks and utilizing e-commerce technology. The product development strategy is carried out through product innovations typical of Islamic boarding schools. Keywords: blue ocean strategy, economic independence, OPOP, pesantren